Potency and Antibacterial Efficacy of Degraded Chloramphenicol in Marketed Eye Drop Preparations (Bangladesh Pharmaceutical Journal, 2015)
This study was done to evaluate the antibacterial activity of chloramphenicol eye drops after exposure to sunlight as well as to measure the percentage of drug content. Chloramphenicol eye drops manufactured by four different companies were collected from local market and exposed to sunlight and their antimicrobial activity was determined against Salmonella typhi and Staphylococcus aureus. Each product was exposed to sunlight for fourteen hours in three different ways with or without of their packaging. The percentage of chloramphenicol contents in eye drop samples was also measured by UV-spectrophotometric method. Significant differences in the inhibitory zones were observed among different set of samples. An inverse correlation between percentage of chloramphenicol content and their antibacterial activity was observed. The results indicate that the UVspectrophotometric method cannot distinguish between chloramphenicol and its degraded products and thus gives incorrect high values of drug content in the preparations, therefore, it should not be considered as an appropriate method to analyze chloramphenicol preparation with its degradation products. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22299 Bangladesh Pharmaceutical Journal 16(2): 165-169, 2013